Exiles : a novel [compact disc, unabridged] - Harper, Jane (Jane Elizabeth) (Harper, Jane (Jane Elizabeth). Aaron Falk., 2023)
Joining a family celebration in Australian wine country, investigator Aaron Falk finds that, between his close friend, a missing mother, and a woman he's drawn to, long-hidden truths begin to emerge.